Improving community-based care for children with a rare condition: The example of long-segment congenital tracheal stenosis and perceptions of health professionals, parents and teachers. (April 2021) - Wray, Jo; Sugarman, Hannah; Davis, Laura; Butler, Colin; McIntyre, Denise; Hewitt, Richard
Abstract: Background: Long segment congenital tracheal stenosis (LSCTS) is a rare, complex condition which is often poorly understood by community-based health professionals (HPs). Anecdotally, such HPs often lack confidence providing care for children, resulting in children being brought to the tertiary centre more frequently than necessary. We wanted to identify the information and support needs of HPs in primary and secondary care looking after a child with LSCTS, the views of those providing education to these children, and elicit parents' perceptions about community-based services, to improve overall care for children and families. Method: Questionnaires were sent to 175 community-based HPs and 34 teachers involved in the care of children with LSCTS. Face-to-face or telephone interviews were conducted with 12 parents of patients with LSCTS to establish their perceptions of community-based services. Results: Ninety (51%) completed questionnaires were returned from HPs and 18 (53%) from teachers. Responses indicated low levels of knowledge of LSCTS. Physical, practical and communication information needs were identified by all respondent groups, together with general and condition-specific concerns. Interviews with parents indicated that they thought the level of knowledge about LSCTS in the community was low, which had a negative impact on their willingness to consult local services. Better information provision for HPs, teachers and parents was identified as a means of improving outcomes. Conclusion: Professionals caring for children with LSCTS in the community and in schools have unmet information and support needs, with consequences for children, families, HCPs in both the community and tertiary hospital, and teachers.